Workshop on Using Microsoft PowerPoint and Canva Platform as Teaching Tools for Teachers to Boost Children’s Learning Enthusiasm in Lembang Public Elementary School - Yulia, Happy; Nurfitriyah, Annisa; Maulana, Cahya; Rosmawia, Rosmawia; Putri, Liza Aulia (Jurnal Pengabdian Masyarakat, 2023)
Purpose: This study highlights the need to enhance teachers' proficiency in Microsoft Office and Canva Platform at Lembang Public Elementary School. The purpose of the workshop was to equip educators with essential skills using these tools, thereby addressing the existing proficiency gap among teachers. Method: The workshop employed a straightforward approach involving material presentation and hands-on exercises. Teachers actively participated, demonstrating an 80% success rate in comprehending and applying the knowledge, validating the effectiveness of the workshop's methodology. Practical Applications: The workshop's outcomes have significant practical implications. Teachers, now adept in these technologies, can effectively integrate them into their teaching methods, enhancing classroom engagement and learning experiences. Additionally, these skills empower teachers in various real-world scenarios, fostering a more interactive and modern educational environment. Conclusion: This study underscores the workshop's success in bridging the proficiency gap among teachers, resulting in a more technologically proficient teaching faculty at Lembang Public Elementary School. The hands-on methodology proved highly effective, ensuring practical application of Microsoft Office and Canva Platform skills in educational settings.